HVDC Transmission Placement Study to Increase Critical Clearing Time Using Sensitivity Analysis - Yogadipha Bagas, I Gede Dyotha; Priyadi, Ardyono; Budiharto, Vita Lystianingrum (JAREE (Journal on Advanced Research in Electrical Engineering), 2024)
Stability is the ability to go back to ordinary conditions after an interruption. Power transfer using an AC transmission system has some stability issues. Fast modulation of the HVDC transmission can escalate the transient stability of interconnected power systems thereby increasing the CCT. To calculate load flow sensitivity, use the load flow sensitivity analysis command in Powerfactory 15.1. The variable considered in this research is dφ/dP. In this paper, we will discuss the use of sensitivity analysis to specify the location of the HVDC transmission to increase the CCT value. By taking several samples that have high sensitivity values,namely channels 8-9 to 7-8 with an average cct change value of 0.555 s, mediumvalues, channels 5-8 to 9-6 have an average cct change of 0.234 s, and low fromchannels 6-4 to 9-4 with an average change of 0.109 s. The data above shows thata channel with a large sensitivity value will provide a higher increase in cct valuecomparedwith a low sensitivityvaluewhen paired with an HVDC.